2015
DOI: 10.1038/nri3839
|View full text |Cite
|
Sign up to set email alerts
|

Perforin and granzymes: function, dysfunction and human pathology

Abstract: A defining property of cytotoxic lymphocytes is their expression and regulated secretion of potent toxins, including the pore-forming protein perforin and serine protease granzymes. Until recently, mechanisms of pore formation and granzyme transfer into the target cell were poorly understood, but advances in structural and cellular biology have now begun to unravel how synergy between perforin and granzymes brings about target cell death. These and other advances are demonstrating the surprisingly broad pathop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
786
1
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 936 publications
(867 citation statements)
references
References 186 publications
13
786
1
4
Order By: Relevance
“…4). In addition to the release of NK-mediated IFN-g in the original protocol to measure NK cell activity, we also measured the release of perforin from NK cells, which is elementary for the killing of infected target cells (Voskoboinik et al, 2015). Overall, we showed that the sera containing a PA titre against HA1 A(H1N1) induced an increase in % IFNg/CD107A-positive NK cells ( Fig.…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 90%
“…4). In addition to the release of NK-mediated IFN-g in the original protocol to measure NK cell activity, we also measured the release of perforin from NK cells, which is elementary for the killing of infected target cells (Voskoboinik et al, 2015). Overall, we showed that the sera containing a PA titre against HA1 A(H1N1) induced an increase in % IFNg/CD107A-positive NK cells ( Fig.…”
Section: Adcc Induction Pre-and Post-a(h1n1)2009 Infectionmentioning
confidence: 90%
“…We also find increased expression of transcripts encoding key regulators of cytotoxic cells including regulator of G Protein Signaling-1 (RGS1), eomesodermin (EOMES), B-cell CLL/lymphoma 11B (zinc finger protein), synuclein, alpha (SNCA), and T cell receptor beta constant 1 (TRBC1), all of which are involved in different aspects of differentiation and proliferation/clonal expansion of effector memory cells [33][34][35][36][37]. Finally, both CD8 + T cells and NK cells have conserved pathways that mediate target allograft cell injury via perforin, granzymes and granulysin, each of which is differentially over-expressed in incipient CLAD cases [38]. It is also of interest that multiple genes related to hemoglobin (HB) expression are increased in the BAL CP from cases of incipient CLAD.…”
Section: Discussionmentioning
confidence: 99%
“…Granzyme B (GrB) is a serine protease that regulates inflammation, apoptosis, and antiviral immunity. 2,3 As such, GrB has also been shown to be a marker of a cell's cytotoxic capacity. 4 The entry of GrB into a cell is facilitated by the pore-forming protein, perforin.…”
Section: Hronic Rhinosinusitis (Crs) Is a Highly Prevalent Inflammamentioning
confidence: 99%